A Descriptive Study to Assess the Awareness on First Aid of Fracture Among Selected Rural Public of Mysuru - Rashmi P.; Suneel Kumar C.N.; Pavitra R. (International Journal of Orthopedic Nursing and Practices, 2023)
First aid refers to the prompt care given to a person who has been suddenly ill or injured until expert help is available or until the individual has recovered. Providing initial care to an individual with a minor injury is classified as first aid, wherein the application of first aid techniques suffices for treating minor burns, wounds, and insect stings. One ailment that requires emergency care is fracture, which will help to prevent subsequent difficulties. If patients who need emergency care are given first aid right away, the outcome can be greatly improved.
Keywords: First aid; emergency care; fracture; ill or injured; public awareness